Uji Daya Hasil Pendahuluan Lima Galur Jagung (Zea mays L.) Hibrida Silang Tunggal Rakitan Politeknik Negeri Lampung - Dian Fitriyani; Jaenudin Kartahadimaja; Nurman Abdul Hakim (Politeknik Negeri Lampung., 2019)
On Research this do Test power the results of the introduction for knowing corn strain the have power the results of the do hight can do make as candidate variety corn hybrid commercial. Research this doing in land of lampung State Polytechnic on April until August 2016 with Randomize Complethy Block Design (RCBD) i.e. five strain corn hybrid A (PL 205 x Pl 401), B (PL 406 x PL 205), C (PL 302 x PL 205), D (PL 205 x PL 406), E (PL 401 x PL 205) and one variety hybrid P21 as comparison . Treatment repeated as much three times and data observations analyzed with us prints range if there are difference among the treatment then will continued with Least Significant Different (LSD) on stage 5%. The results of this study were (1). The E strain has a higher potential than the A, B, C, D, and Pioner 21 (P 21) strains. (2) A, B, and C strains have the same result as hybrid varieties of P21.